PCR-based molecular detection and in silico partial characterization of patatin-like gene in cucumber (Cucumis sativus cv. bituin) - De Vera, Joselito Yee, Jr. (Animo Repository, 2004)
A variety of cucumber (Cucumis sativus vars. bituin) belonging to Family Solanaceae was screened using PCR-based molecular techniques to detect the presence of a highly conserved, defense-related and a suspected potent allergen gene: the patatin-like gene. In this preliminary study, PCR was used to amplify patatin-like sequence with primer pair B [42-mer] and N [33-mer]. Primer pair B&N, which amplifies the full-length gene (of 1182bp size of Hev b 7), amplified similar-sized DNA fragment (~1.2Kb) in the sample variety tested. The DNA fragment amplified from cucumber var. bituin (CBT) was further confirmed by sequencing. It had 99% homology in DNA-DNA sequence comparison (with 1010bp) and a 95% protein sequence homology (with 330 amino acids) with Hev b 7, a known latex allergen, which served as the control. A comparison was made with Hev b 7 (388 amino acids) and patatin (T5 precursor protein) (386 amino acids) sequences. Both Hev b 7 and CBT sequences have 37% and 39% sequence identities with patatin (Blastx results), respectively. The CBT sequence obtained 40% pairwise sequence identities with patatin T5 precursor sequence and 62% weighted similarity. Initial characterization of the CBT DNA and protein sequence structure and properties using in silico methods were also performed. It had 35 percentage pairwise identities and 54 percentage of similarity to the known patatin third domain (1oxwC). The translated amino acid had several identified motifs like: N- glycosylation sites, protein kinase C phosphorylation sites, Casein kinase II phosphorylation sites, single tryrosine kinase phosphorylation site, N-myristoylation site, a leucine zipper pattern and Ser residue in lipid acyl hydrolase motif. There are 10 out of 11 identified similar antigenic epitopes, with one unique antigenic epitope in CBT sequence as compared to Hev b 7. The confirmed presence of the patatin-like gene and a potential allergen from CBT gives an initial identification of more concrete background as future reference for other related studies.